Evaluation of Restrictions on Land Tenure by Private Legal Entities in the Context of Location Permits and Cultivation Rights: An Analysis of the Unclear Norms in the Regulation of the Minister of ATR/BPN - Dinalara Dermawati Butarbutar; Rachmad Saafa’at; Iwan Permadi; Mohammad Hamidi Masyukur (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
The issue of limiting land ownership by private legal entities, particularly limited liability companies (PTs), has become an important concern in agrarian policy in Indonesia, particularly in the plantation sector. Although there are regulations governing the maximum limit of land ownership, their implementation remains unclear, especially regarding Cultivation Rights Title (CRT) and location permits. This ambiguity allows large companies to control vast tracts of land, exacerbating inequality and marginalizing smallholders. This study aims to analyze the normative ambiguities in land tenure restrictions, particularly related to CRT and location permits, and assess their implications for land distribution and smallholder welfare. The research seeks to explore the need for stricter and clearer regulations to promote equitable distribution of land ownership and align agrarian policy with the principles of social justice mandated by the 1945 Constitution. A normative juridical approach was used, focusing on analyzing the legal norms governing restrictions on land ownership by private legal entities in the plantation sector. The study found that ambiguities in the regulations, especially those under the Ministerial Regulation of ATR/BPN, have created legal uncertainty regarding the area of land that can be controlled by private legal entities. Restrictions based solely on business type and commodity allow large companies to monopolize land, disadvantaging smallholders and exacerbating inequality in land distribution. This research has implications highlighting the need for comprehensive policy reforms with clearer and stricter land ownership restrictions to ensure a more equitable distribution of land.